Peran Perempuan dalam Ketahanan Keluarga: Studi Kasus Pada Keluarga di Pedesaan Sunda - Fajar, Rezky; Herawati, Erna; Yulianingsih, Yulianingsih (Umbara, 2023)
Women’s role in family resilience has never ended. Even, their roles keep increasing and changing over time while remaining unexplored. This research discusses women’s role in family resilience drawing from the case of women cadres and non-cadres who were involved in the program for family resilience run by P2WKSS (women’s organization at village level). This research used a qualitative method and employed interviews and direct and participant observation to collect data in Cidadap Village in West Java. Data of this research were analyzed based on indicators of women’s role in the  family development and resilience, named iBangga (Indonesian Family Development Indexes).  This research  found  some important findings on women’s role in family resilience in the context of Sundanese culture in West Java. Women’s position in the family based on Sundanese gender norms, put them in the dominant and crucial roles in family resilience. In the family, women play roles as mothers and as wives; and they are responsible to maintain the family order and peace;  and to raise the children; while at the same time must serve their husband. In society, they are responsible to preserve gender norms and values and transmit it to the next generations. They also become the pioneer in the government program implemented in the village which targets to improve family resilience.